Tackling gender inequality in a climate-changed world: How agrifood and social protection systems can empower women and girls to build climate resilience - Ceravolo, Clara; Sisto, Ilaria; Whitehead, Lauren; Walsham, Matthew; Verhoeven, Morane; Roy, Shalini (United Nations Children's Fund, 2024)
Air pollution, rising temperatures, crop failures, and water shortages are increasing pressures on health and agrifood systems. During these crises, households often reduce food consumption, sell assets, migrate or adjust labor allocation between men and women. Women and children are at greater risk of food insecurity due to lower access to and control of productive resources, services, household decision-making, income allocation, and perceived expendability.